If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2xy + 1 = 11 Reorder the terms: 1 + 2xy = 11 Solving 1 + 2xy = 11 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + 2xy = 11 + -1 Combine like terms: 1 + -1 = 0 0 + 2xy = 11 + -1 2xy = 11 + -1 Combine like terms: 11 + -1 = 10 2xy = 10 Divide each side by '2y'. x = 5y-1 Simplifying x = 5y-1
| 13x^2+13x-33=-33 | | 12=2Q-2.6 | | 4a+8b=100whatisA | | 2x+15=24 | | 3x-8-2x=8x+20 | | 7ab+2ba= | | 5x-5=13+2x | | 3x-8-2x=8x+30 | | (x+4)x(23-x)=0 | | 14x^2+8x-21=0 | | 14x^2+18x-21=0 | | a=18+4a | | 3y^2-10y-25=0 | | 2x+(3x+1)=4 | | 7y^2-30y+8=0 | | 5(3+4x)-6=129 | | 7y^2+30y+8=0 | | -9-24+9-18= | | 4(3x-1)=42 | | a+15=14 | | 14=q/8 | | 3x(5x-2)+5x-2=0 | | 14=q/10 | | 14=q/5 | | 120-21x=9x | | 0.13*x+14.95=50 | | 30+y+8=118-3y | | 4m-1=3m+2 | | (3+x)3=15+x | | 12+7x=15-6(3-2x) | | 5x-19=11+3x | | 13x-7=11+4x |